The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3928/00989134-20120207-03
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Desired Patterns of Communication with Nursing Home Staff— Just TALKKK!

Abstract: Individuals with cognitive impairment often represent a significant percentage of the residents in a nursing home nurse's care. With years of experience caring for their placed family members, caregivers of these residents are often experts in knowing the resident's needs, habits, behaviors, and moods. Caregivers often wish to convey this insider knowledge to nursing home staff. Furthermore, communication with caregivers promotes trust that personalized, safe, and effective care occurs when they are not there.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…For example, the use of caregiver stories, such as those provided in this article, provide specific exemplars for discussion during an educational activity. Other interventions for preservation of personhood in the long-term care setting include encouraging family members to bring in photos and personal items, and to share their knowledge 9 about the routines, moods, behaviors, wants, and needs of the person with dementia. Promising techniques to create or enhance awareness of the personhood of residents with dementia and foster relationships include the use of drama 17 , storytelling 18 , and metaphors 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of caregiver stories, such as those provided in this article, provide specific exemplars for discussion during an educational activity. Other interventions for preservation of personhood in the long-term care setting include encouraging family members to bring in photos and personal items, and to share their knowledge 9 about the routines, moods, behaviors, wants, and needs of the person with dementia. Promising techniques to create or enhance awareness of the personhood of residents with dementia and foster relationships include the use of drama 17 , storytelling 18 , and metaphors 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Photos, personalized items, stories, and observations from family members can foster understanding of the resident’s past, relationships, needs, and preferences. One study of family caregivers’ experiences following long-term care placement found that caregivers desired to be asked for their knowledge about the needs, behaviors, and routines of their family members and to be listened to when they offered advice 9 .…”
mentioning
confidence: 99%
“…While the HPPs’ expressed their deep appreciation and respect for the partners, who provide support over an extended period of time, they were caught in tension about how to support this. The literature has revealed that care givers find it meaningful to be recognised, valued and respected in their engagement with health professionals (Birgersson & Edberg, 2004; Jenkinson et al, 2012; Lindahl et al, 2011; McLaughlin et al, 2011; Palmer, 2012). Unfortunately, the acknowledgement and admiration expressed by HPPs in the current study did not always align with the experience of spousal care givers in the literature, or in Bolland et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…9 The TALKKK acronym can remind physicians about process-oriented communication with families (see Figure 2). 19 Prior to facility placement, family members were often caregivers, so physicians should involve the family in treatment decisions or recommendations. 9 Families respond well to a physician who knows their loved one and demonstrates effective bedside manner.…”
Section: The Trinity Of Carementioning
confidence: 99%
“…9 Families respond well to a physician who knows their loved one and demonstrates effective bedside manner. 19 Many physicians will need training and observed practice to develop appropriate bedside skills when working with older adults.…”
Section: The Trinity Of Carementioning
confidence: 99%